2002
DOI: 10.1111/1467-9280.00497
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Orientation Induces Neglect-Like Lateral Biases in Covert Attention

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 18 publications
4
55
4
1
Order By: Relevance
“…However, Grubb and Reed (2002) were able to induce pseudoneglect in a covert attention task by leftward rotation of the torso. Hasselbach-Heitzeg and Reuter-Lorenz (2002) also found that rightward rotation reduced response times for targets on the right.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, Grubb and Reed (2002) were able to induce pseudoneglect in a covert attention task by leftward rotation of the torso. Hasselbach-Heitzeg and Reuter-Lorenz (2002) also found that rightward rotation reduced response times for targets on the right.…”
Section: Discussionmentioning
confidence: 91%
“…Research on spatial representation suggests independent motivation for such an ultimate frame being anchored to the head (e.g., Avillac, Denève, Olivier, Pouget, & Duhamel, 2005) or to the torso (e.g., Grubb & Reed, 2002;Karnath, Schenkel, & Fischer, 1991). A key motivation for a head-centric hypothesis is the number and significance of the sensory organs found in the head: the eyes, ears, and the vestibular labyrinth.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Karnath et al (1991) and Karnath (1994), Grubb and Reed (2002) reported an effect of trunk orientation on covert orienting in healthy controls. Grubb and Reed (2002) argued that previous studies did not isolate the attentional mechanism that is most strongly impaired in HSN: the disengagement of attention from one side of space that is necessary to shift attention toward the location of a new salient event (Posner, Walker, Friederiech, & Rafal, 1984).…”
mentioning
confidence: 58%
“…Grubb and Reed (2002) argued that previous studies did not isolate the attentional mechanism that is most strongly impaired in HSN: the disengagement of attention from one side of space that is necessary to shift attention toward the location of a new salient event (Posner, Walker, Friederiech, & Rafal, 1984). An impairment of attentional disengagement, inferred from excessively long response times for invalidly cued targets in the contralesional half of space (Losier & Klein, 2001), has been proposed to be characteristic of HSN patients (Posner et al, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation